Priming Applications with Mosquito (Diptera: Culicidae) Larva Rearing Water in White Cabbage Seeds (Brassica oleracea L. var. capitata F. alba cv. Yalova 1) - Şahin, Nihan; Arın, Levent; Uludağ, Mehmet; Şakacı, Zafer; Kar, Sırrı (International Journal of Environment, Agriculture and Biotechnology, 2022)
The starting material with good quality is a portent of a satisfactory and good harvest in vegetables grown from seedlings such as cabbage, a good beginning makes a good ending. Seed pre-applications promote uniform and rapid germination/emergence, leading to strong seedling formation. In this study, bio-based larval rearing water was used as an organic priming agent and its effect was compared with the effects of hydro priming. As a result of the study, the effects of both priming applications on germination and emergence were superior to the untreated control in terms of mean time and vigor, but there were no differences according to germination and emergence percentages. According to mean time of germination organic primed seeds germinated in the shortest time with 2.45 days compared to hydro primed seeds (2.77 days) and control (3.48 days). Likewise, this, organic primed seeds were emergence in 6.80 days, hydro primed seeds were emergence in 7.19 days and control seeds were emergence in 7.39 days. Vigor index of germination was 19.09 in organic priming, but it was 17.48 in hydro priming and 14.56 in control. On the other hand, vigor index of emergence was 6.39 in organic priming, 5.67 in control and, 5.28 in hydro priming applications. In addition, organic priming came to the fore among organic priming and hydro priming. It is thought that this positive effect may be due to the nitrogen and organic carbon content of larval rearing water.